2015
DOI: 10.1002/anie.201411450
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Shell Carbon‐Encapsulated Iron Nanoparticles: Synthesis and High Electrocatalytic Activity for Hydrogen Evolution Reaction

Abstract: Efficient hydrogen evolution reaction (HER) through effective and inexpensive electrocatalysts is a valuable approach for clean and renewable energy systems. Here, single-shell carbon-encapsulated iron nanoparticles (SCEINs) decorated on single-walled carbon nanotubes (SWNTs) are introduced as a novel highly active and durable non-noble-metal catalyst for the HER. This catalyst exhibits catalytic properties superior to previously studied nonprecious materials and comparable to those of platinum. The SCEIN/SWNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
191
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(203 citation statements)
references
References 43 publications
11
191
0
1
Order By: Relevance
“…15 for details). This finding is consistent with other recent reports on Fe-based electrocatalysts3349. The values of the mean-square relative displacement for Fe–Fe pairs were slightly larger for the H 2 -treated catalyst compared with Fe foil, indicating the presence of larger structural disorder, which is expected in small particles.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…15 for details). This finding is consistent with other recent reports on Fe-based electrocatalysts3349. The values of the mean-square relative displacement for Fe–Fe pairs were slightly larger for the H 2 -treated catalyst compared with Fe foil, indicating the presence of larger structural disorder, which is expected in small particles.…”
Section: Resultssupporting
confidence: 92%
“…In this case, the donation of electron density from the Fe particle to the carbon shell allows for efficient ORR catalysis. This model for shell-encapsulated Fe nanoparticles has been implicated in the hydrogen evolution reaction, where DFT suggests that electron density is donated from the Fe particle to individual atoms in the graphitic shell4954. DFT calculations have also been used to explain the catalytic activity of encapsulated Fe particles for the ORR that are present in many NPM ORR catalysts29.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Tafel plots depicted in Figure 5(b) were calculated to get an insight into the HER kinetic processes of the catalysts. The Pt/C catalyst shows a Tafel slope of 31.2 mV dec −1 , which is consistent with the reported values [11, 26]. The Tafel slope of Ba 0.95 CFZY is 80.4 mV dec −1 , which is lower than those of Ba 0.99 CFZY (85.9 mV dec −1 ), BaCFZY (87.5 mV dec −1 ), and BSCF (92.0 mV dec −1 ).…”
Section: Resultssupporting
confidence: 90%
“…The first step is a Volmer reaction (H 2 O + e −  → H ads  + OH − ), in which the water molecule adsorbed on the catalyst surface is ionized and transferred to be H ads . The second step is either a Heyrovsky reaction (H 2 O + H ads  + e −  → H 2  + OH − ) or a Tafel reaction (H ads  + H ads  → H 2 ) [26]. Both of the HER pathways (Volmer-Heyrovsky or Volmer-Tafel pathway) involved the adsorption of water molecules on the active sites, electrochemical reduction of adsorbed water molecules into adsorbed hydroxyl ions (OH − ) and H ads , desorption of OH − to refresh the catalyst surface, and formation of H ads for H 2 generation [7].…”
Section: Resultsmentioning
confidence: 99%
“…38 Last but not least, a recent study reported on the high HER activity of 2-3 nm iron nanoparticles encapsulated in singleshell or few-shell graphitized carbon layers. 76 In 0.5 M H 2 SO 4 , the potential necessary to reach −1 mA·cm −2 was ca −35 mV vs. RHE. In addition, the Tafel slope for HER of their iron based catalyst was only 40 mV·dec −1 , comparable to that for HER on Pt.…”
mentioning
confidence: 92%